Multifunctional Derivatives of Spiropyrrolidine Tethered Indeno-Quinoxaline Heterocyclic Hybrids as Potent Antimicrobial, Antioxidant and Antidiabetic Agents: Design, Synthesis, In Vitro and In Silico Approaches - Nouha Bouali; Manel Ben Hammouda; Iqrar Ahmad; Siwar Ghannay; Amira Thouri; Amal Dbeibia; Harun Patel; Walid Sabri Hamadou; Karim Hosni; Mejdi Snoussi; Mohd Adnan; Md Imtaiyaz Hassan; et al. (Molecules, 2022)
To combat emerging antimicrobial-resistant microbes, there is an urgent need to develop new antimicrobials with better therapeutic profiles. For this, a series of 13 new spiropyrrolidine derivatives were designed, synthesized, characterized and evaluated for their in vitro antimicrobial, antioxidant and antidiabetic potential. Antimicrobial results revealed that the designed compounds displayed good activity against clinical isolated strains, with 5d being the most potent (MIC 3.95 mM against Staphylococcus aureus ATCC 25923) compared to tetracycline (MIC 576.01 mM). The antioxidant activity was assessed by trapping DPPH, ABTS and FRAP assays. The results suggest remarkable antioxidant potential of all synthesized compounds, particularly 5c, exhibiting the strongest activity with IC50 of 3.26 ± 0.32 mM (DPPH), 7.03 ± 0.07 mM (ABTS) and 3.69 ± 0.72 mM (FRAP). Tested for their α-amylase inhibitory effect, the examined analogues display a variable degree of α-amylase activity with IC50 ranging between 0.55 ± 0.38 mM and 2.19 ± 0.23 mM compared to acarbose (IC50 1.19 ± 0.02 mM), with the most active compounds being 5d, followed by 5c and 5j, affording IC50 of 0.55 ± 0.38 mM, 0.92 ± 0.10 mM, and 0.95 ± 0.14 mM, respectively. Preliminary structure–activity relationships revealed the importance of such substituents in enhancing the activity. Furthermore, the ADME screening test was applied to optimize the physicochemical properties and determine their drug-like characteristics. Binding interactions and stability between ligands and active residues of the investigated enzymes were confirmed through molecular docking and dynamic simulation study. These findings provided guidance for further developing leading new spiropyrrolidine scaffolds with improved dual antimicrobial and antidiabetic activities.